Who was the first to visualize the malaria parasite? - Emmanuel Drouin; Patrick Hautecoeur; Miles Markus (Parasites & Vectors, 2024)
Abstract Human malaria, an ancient tropical disease, is caused by infection with protozoan parasites belonging to the genus Plasmodium and is transmitted by female mosquitoes of the genus Anopheles. Our understanding of human malaria parasites began officially in 1880 with their discovery in the blood of malaria patients by Charles Louis Alphonse Lavéran (1845–1922), a French army officer working in Algeria. A claim for priority was made by Philipp Friedrich Hermann Klencke (1813–1881) in 1843, who wrote a chapter entitled: “Marvellous parallelism between the manifestations of vertigo and the presence of animalcule vacuoles in living blood.” We should not lose sight of this old controversy, which is rarely mentioned in historical reviews on malaria. Graphical Abstract